A Simplified and Cheapest Method for the Diagnosis of Sickle Cell using Whole Blood PCR and RFLP in Nepal - Tripathi, Giri Raj (Tribhuvan University Journal, 2016)
Sickle cell anemia is a serious genetic health problem dominated in Tharu community of western Nepal. Molecular methods like PCR and RFLP are the best method to identify Sickle c ell anemia trait. Molecular analysis needed many steps and expensive chemicals and Kits. The aim of this research was to develop a simple and cheapest method to process from whole blood sample for the polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) without the use of expensive reagents and Kits. In this study molecular identification of sickle cell traits is subjects using whole blood PCR and RFLP were carried out. Venous blood samples collected from 800 individuals were provided by Nepal Health Research Council (NHRC). All the obtained samples were frozen at –80°C, and then rapidly thawed at 37°C. Then the samples were transferred to 2 ml eppendrof tube and boiled for 10minutes in distilled water and centrifuged at 12000 rpm for 2 minute. The supernatant was then used directly for PCR and RFLP. For comparison, purified DNA from the QIAGEN genomic DNA extraction kit was used as control. PCR/RFLP results using the whole blood boiling method was qualitatively similar to DNA extracted by using commercial Kits. The research demonstrates that whole blood PCR and RFLP method is simple and cheaper way for molecular diagnosis of sickle cell traits in human.